Growth in the ecological transition: green, zero or de-growth? - Jan Priewe (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
The article discusses the ongoing transition to climate neutrality in 2050 with a focus on the options of green growth, zero growth or de-growth. First, the stylised facts about the greenhouse effect and the status quo are shown with special attention to emerging economies as key contributors to greenhouse gas emissions since 1990. Globally, brown growth is still predominant. Since the Global South has to reduce emissions as much as the Global North, the resource-rich countries in the South face the gravest challenges. Second, different scenarios of the global transition with different combinations of GDP growth and reduction rates of the emission-to-GDP ratio are shown. The result is that both variables are important, but the reduction of the emissions ratio is more important than growth. Zero growth per se is not necessarily effective in reaching the Paris goals. Third, low green growth in the North is advised (under certain conditions also zero growth), and moderate green growth in the South. Zero growth without capital accumulation in a closed economy would terminate capitalism in its common definition, in contrast to zero growth in an open economy. Third, proposals from ecological economics for zero growth and de-growth are diverse and involve significant shortcomings, especially regarding the macroeconomic analysis.
Keywords: 330; transition; growth theory; energy economics; decarbonisation; zero growth; de-growth; climate change; carbon prices; capitalismO47; P18; P28; P47; Q01